La omega y el alfa del Proceso Penal Juvenil en Costa Rica: La fase de ejecución - Burgos Mata, Álvaro (2014)
The judgment and its execution are not the end of the criminal proceeding; on the contrary, they are probably the beginning of the most critical and important stage that the inmate will have to go through from the criminological point of view.